2014
DOI: 10.1002/2055-5822.12003
|View full text |Cite
|
Sign up to set email alerts
|

The late sodium current in heart failure: pathophysiology and clinical relevance

Abstract: Large and growing body of data suggest that an increased late sodium current (I Na,late ) can have a significant pathophysiological role in heart failure and other heart diseases. The first goal of this article is to describe how I Na,late functions under physiological circumstances. The second goal is to show the wide range of cellular mechanisms that can increase I Na,late in cardiac disease, and also to describe how the up-regulated I Na,late contributes to the pathophysiology of heart failure. The final se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 180 publications
0
15
0
Order By: Relevance
“…This may be related to the well-known fact that ATX-II slows inactivation of Na + channels [33]. ATX-II is widely used for mimicking pharmacologically the consequences of an augmented I Nalate , which is often seen under pathological conditions [5] and ATX-II is a widely used pharmacological tool to model this. In canine myocytes (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be related to the well-known fact that ATX-II slows inactivation of Na + channels [33]. ATX-II is widely used for mimicking pharmacologically the consequences of an augmented I Nalate , which is often seen under pathological conditions [5] and ATX-II is a widely used pharmacological tool to model this. In canine myocytes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the elevation of I Na-late results in increased arrhythmia propensity (e.g. in heart failure) including prolongation of the action potential duration (APD), increased inhomogeneity of repolarization and occurrence of early as well as delayed afterdepolarizations [5,[12][13][14]. Therefore, as a new concept, intensive efforts were made recently to develop selective inhibitors of I Na-late [9,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…To validate the "#% model equation, simulated current-voltage relationship (I-V curve) were compared to experimental data as shown in Figure 1. The conductance of the WT "#% was chosen to be 0.5% of that of "#$ illustrated in literature [14,15]. Specifically, the model of the "#% was given by the following equation:…”
Section: Methodsmentioning
confidence: 99%
“…5 The transient mode is responsible for the peak Na + current (I Na ) during phase 0 and lasts for about 1 ms. 5,6 After the peak I Na , Na + channels quickly become inactivated, resulting in the burst and late-scattered modes responsible for a sustained current component that lasts up to 100 ms during the plateau phase of action potential and is referred to as ''late I Na '' (Figure 1). 7 The amplitude of late I Na represents 0.1% to 1% of that of peak I Na ; however, because of the relatively longer duration of plateau phase 2 compared with phase 0, the net late Na + influx is comparable with the peak Na + influx. 8,9 Role of Late I Na Current in Atrial and Ventricular Arrhythmias Enhanced late I Na in atrial myocytes has been shown to lower the threshold of action potential firing, initiate diastolic depolarization, and increase excitability, and hence the risk of atrial arrhythmias, mainly atrial fibrillation (AF; Figure 2).…”
Section: Biology Of the Sodium Channelsmentioning
confidence: 97%
“…8,9 Role of Late I Na Current in Atrial and Ventricular Arrhythmias Enhanced late I Na in atrial myocytes has been shown to lower the threshold of action potential firing, initiate diastolic depolarization, and increase excitability, and hence the risk of atrial arrhythmias, mainly atrial fibrillation (AF; Figure 2). 7 On the other side, several electrophysiological mechanisms result in the initiation of ventricular arrhythmias, including triggered activity (which is either early after depolarization [EAD] or delayed after depolarization [DAD]), abnormal automaticity, and reentry. 10 Patients with cardiomyopathies may have increased transmural dispersion of repolarization (TDR), which is considered one of the Figure 1.…”
Section: Biology Of the Sodium Channelsmentioning
confidence: 99%